The Concept of Wastes to Energy Using Sugary Wastes - Sarwar, Fiza; Malik, Wajeeha; Ahmed, Muhammad Salman; Shahid, Harja (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Abstract: This study was designed using actual effluent from the sugary mills in an Up-flow Anaerobic Sludge Blanket (UASB) Reactor to evaluate treatability performance. The reactor was started-up in step-wise loading rates beginning from 0.05kg carbon oxygen demand (COD)/m3-day to 3.50kg-COD/m3-day. The hydraulic retention time (HRT) was slowly decreased from 96 hrs to eight hrs. It was observed that the removal efficiency of COD of more than 73% can be easily achieved at an HRT of more than 16 hours corresponding to an average organic loading rate (OLR) of 3.0kg-COD/m3-day, at neutral pH and constant temperature of 29°C. The average VFAs (volatile fatty acids) and biogas production was observed as 560mg/L and 1.6L/g-CODrem-d, respectively. The average methane composition was estimated as 62%. The results of this study suggest that the treatment of sugar mills effluent with the anaerobic technology seems to be more reliable, effective and economical. DOI: http://dx.doi.org/10.3126/hn.v9i0.7075 Hydro Nepal Vol.9 July 2011 57-62